Data rules reinventing the market economy - Alaimo, Cristina; Kallinikos, Jannis (The MIT Press, 2024)
"A road map to understanding the digital economy of social media platforms"--
Keywords: Digitale Daten; Digitalisierung; Big Data; Wirtschaft; Electronic Commerce; Marktwirtschaft; Electronic commerce; Social media / Economic aspects; Commerce électronique; Médias sociaux / Aspect économique